Factors associated with hypertension stages among Malaysian adults using secondary data from national health and morbidity survey 2015 - Naidu, Balkish Mahadir (2018)
Introduction: High blood pressure is a world’s classic problem and remains a major global health burden. Either singly or combined with other metabolic diseases, high blood pressure increased the risk of cardiovascular diseases. The epidemic was responsible for 7.4 million deaths due to coronary heart disease, and 6.7 million deaths due to stroke. Objective: The objectives of this study was to determine the prevalence of hypertension by stages and factors associated with hypertension stages among the adult population in Malaysia. Methods: The study used secondary data from the nationwide cross-sectional populationbased survey using multistage stratified cluster sampling of the National Health and Morbidity Survey 2015. Socio-demographic factors, clinical parameters, behavioural characteristics and comorbidities risk factors were available for analysis. The average blood pressure reading was categorised to four groups according to The 7th Report of The Joint Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure (JNC7) (normal, prehypertension, stage 1 hypertension and stage 2 hypertension). Complex Sample Ordinal Logistic Regression was used for analysis. Results: A total of 15,738 adults were included in the study with the mean age of 41.10 years (15.6 years). The prevalence of prehypertension, stage 1 hypertension and stage 2hypertension were 45.8% (95% CI: 44.66, 47.97), 15.1% (95% CI: 14.34, 15.92) and 5.9% (95% CI: 5.44, 6.41), respectively. Factors associated with more severe hypertension were observed among those in 30–39 years old (OR = 1.68, 95% CI: 1.47, 1.93), 40–49 years old (OR = 2.92, 95% CI: 2.53, 3.36), 50–59 years old (OR = 4.67, 95% CI: 3.97, 5.49), 60 years old and above (OR = 8.09, 95% CI: 6.7, 9.76), rural residents (OR = 1.15, 95% CI: 1.02, 1.28), male (OR = 2.15, 95% CI: 1.95, 2.38), the Malays (OR = 1.23, 95% CI: 1.07, 1.41), had non-formal education (OR = 1.73, 95% CI: 1.37, 2.20), had primary education (OR = 1.41, 95% CI: 1.21, 1.64), had low income (OR = 1.31, 95% CI: 1.12, 1.53), married person (OR = 0.86, 95% CI: 0.77, 0.98), current smoker (OR = 0.84, 95% CI: 0.76, 0.94), were physically inactive (OR = 0.91, 95% CI: 0.83, 0.97), had Diabetes Mellitus (OR = 1.24, 95% CI: 1.10, 1.39), being overweight (OR = 2.06, 95% CI: 1.88, 2.26) and being obese (OR = 4.58, 95% CI: 4.03, 5.21). Conclusion: Complex Sample Ordinal regression analysis revealed that age, locality, gender, ethnic, income, educational level, marital status, Diabetes Mellitus and BMI were the independent factors associated with severity of hypertension.